Descriptive Account of Spanish Loanword Phonology in Kaqchikel - Adell, Eric (Kansas Working Papers in Linguistics, 2013)
This paper examines Spanish loanwords in Kaqchikel from both diachronic and synchronic perspectives. This paper is, to my knowledge, the first descriptive account of any length concerning Spanish loanword phonology in Kaqchikel. The section pertaining to a diachronic perspective of Spanish loanwords examines observable assimilatory processes by which Spanish words may have entered the Kaqchikel lexicon.